PKM PENDAMPINGAN PENGELOLAAN MENU UNTUK AKSELERASI BUMDES KERTA RAHAYU DESA LUMBUNG KECAMATAN SELEMADEG BARAT KABUPATEN TABANAN, BALI - IWK Tejasukmana; Ni Putu Dyah Krismawintari; Ni Luh Putu Suarmi Sri Patni; I Gede Agus Mertayasa; I Gusti Bagus Rai Utama; I Nyoman Tingkes (Bajang Institute, 2025)
This community partnership program explores the development of the Village-Owned Enterprise (BUMDes) Kerta Rahayu in Lumbung Village, Tabanan, which operates in the culinary sector to support local tourism. Although BUMDes has great potential, challenges in management and menu variation remain major obstacles. Through this partnership initiative, the PKM program aims to enhance the managerial capacity of the BUMDes administrators by providing training on culinary business management and menu development. The methods used include socialization, training sessions, and evaluation activities involving administrators and local community members. The results of the training indicate significant improvements in participants’ knowledge and skills in designing and preparing menus, as well as a better understanding of the importance of menu variety to attract tourists. The implications of this program affirm that good management and continuous menu innovation are essential to increasing the appeal of culinary businesses in Lumbung Village, especially in response to the growing number of visitors. Thus, this community empowerment program successfully achieved its objectives and has provided positive impacts for the managers of BUMDes Kerta Rahayu.